2004
DOI: 10.1002/art.20269
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mesenchymal progenitor cells in normal and osteoarthritic human articular cartilage

Abstract: Objective. To determine the presence of mesenchymal progenitor cells (MPCs) in human articular cartilage.Methods. Primary cell cultures established from normal and osteoarthritic (OA) human knee articular cartilage were analyzed for the expression of CD105 and CD166, cell surface markers whose coexpression defines mesenchymal stem cells (MSCs) in bone marrow and perichondrium. The potential of cartilage cells to differentiate to adipogenic, osteogenic, and chondrogenic lineages was analyzed after immunomagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
418
5
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 475 publications
(465 citation statements)
references
References 64 publications
31
418
5
11
Order By: Relevance
“…A more recent study has confirmed that de-differentiated adult human chondrocytes represent a population of multipotent cells capable to differentiate into adipogenic, osteogenic, chondrogenic, myogenic and neurogenic lineages [156]. Finally, the presence and characteristics of MSCs isolated from the cartilage of OA patients were examined [157]. While both MSCs isolated from healthy donors and MSCs have been tested directly for the repair of OA knees in humans [159].…”
Section: Vivomentioning
confidence: 99%
“…A more recent study has confirmed that de-differentiated adult human chondrocytes represent a population of multipotent cells capable to differentiate into adipogenic, osteogenic, chondrogenic, myogenic and neurogenic lineages [156]. Finally, the presence and characteristics of MSCs isolated from the cartilage of OA patients were examined [157]. While both MSCs isolated from healthy donors and MSCs have been tested directly for the repair of OA knees in humans [159].…”
Section: Vivomentioning
confidence: 99%
“…This weakness in cartilage repair capacity highlights the need for novel treatments using tissue engineering and regenerative medicine and new regenerative strategies involving stimulation of articular cartilage repair in vivo (18). Indeed, it has been shown that adult MSC-like progenitors also exist in the cartilage tissue and that their abundance in arthritic cartilage is elevated (19). The lack of regeneration in cartilage can be due to the ongoing inflammatory microenvironment that occurs during the course of osteoarthritis and rheumatoid arthritis.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Recently, the presence of progenitor cells in human articular cartilage has been extensively investigated [13][14][15]. Although articular cartilage develops only from embryonic mesenchyme and intervertebral discs develop from the notochord as well, these two share similarities in cellular phenotype and extracellular matrix composition [16].…”
Section: Introductionmentioning
confidence: 99%